Motor function daily living skills 5 years after paediatric arterial ischaemic stroke: a prospective longitudinal study. (30th May 2018) - Cooper, Anna N; Anderson, Vicki; Greenham, Mardee; Hearps, Stephen; Hunt, Rod W; Mackay, Mark T; Ditchfield, Michael; Coleman, Lee; Monagle, Paul; Gordon, Anne L
Abstract : Aim: To describe 5‐year motor and functional outcomes after paediatric arterial ischaemic stroke (AIS) and to explore factors associated with poorer long‐term outcome. Method: Thirty‐three children (21 males, 12 females) with AIS were recruited to a single‐site, cross‐sectional study, from a previously reported prospective longitudinal stroke outcome study. Children were stratified according to age at diagnosis: neonates (≤30d), preschool (>30d–5y), and school age (≥5y). Motor and functional outcomes were measured at 5 years after stroke. Neurological outcomes were evaluated using the Pediatric Stroke Outcome Measure (PSOM) at 1 month and more than 4 years after stroke. Results: At 5 years after stroke, motor function, quality of life, fatigue, adaptive behaviour, activities of daily living, and handwriting speed were significantly poorer than age expectations. The preschool group had the highest percentage of fine and gross motor impairment. Poorer fine motor skills were associated with subcortical‐only lesions and large lesion size. Poorer gross motor outcomes correlated with preschool age, bilateral lesions, and PSOM impairment at 1 month. Interpretation: Children are at elevated risk for motor and functional impairments after AIS, with the preschool age group most vulnerable. Identifying early predictors of poorer outcomes facilitates targeted early intervention and long‐term rehabilitation. What this paper adds: Following paediatric stroke, children are at elevated risk of motor and functional difficulties. Stroke occurring between 30 days and 5 years of age may result in poorer motor and functional outcomes. What this paper adds: Following paediatric stroke, children are at elevated risk of motor and functional difficulties. Stroke occurring between 30 days and 5 years of age may result in poorer motor and functional outcomes. This article is commented on by Roggeman and Truyers on pages111–112 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.